2014
DOI: 10.1039/c3cc49856e
|View full text |Cite
|
Sign up to set email alerts
|

P2-type Na2/3Ni1/3Mn2/3−xTixO2 as a new positive electrode for higher energy Na-ion batteries

Abstract: New electrode materials of layered oxides, Na2/3Ni1/3Mn2/3-xTixO2 (0 ≤ x ≤ 2/3), are successfully synthesized, and their electrochemical performance is examined in aprotic Na cells. A Na//Na2/3Ni1/3Mn1/2Ti1/6O2 cell delivers 127 mA h g(-1) of reversible capacity and the average voltage reaches 3.7 V at first discharge with good capacity retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
323
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 357 publications
(346 citation statements)
references
References 20 publications
22
323
1
Order By: Relevance
“…[1][2][3][4][5] In the past several years, various intercalation materials for the Na-ion batteries have been extensively investigated. [6][7][8][9][10] Especially, electrode performance of layered sodium transition metal oxides, which was originally studied as positive electrode materials for Na batteries in 1980s, have been significantly improved by the latest battery technology developed in the Li-ion battery system during the past three decades. [11][12][13][14] Their electrochemical properties in the Na cells have been clarified in detail and it was found that some layered materials can deliver large reversible capacity with good redox reversibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] In the past several years, various intercalation materials for the Na-ion batteries have been extensively investigated. [6][7][8][9][10] Especially, electrode performance of layered sodium transition metal oxides, which was originally studied as positive electrode materials for Na batteries in 1980s, have been significantly improved by the latest battery technology developed in the Li-ion battery system during the past three decades. [11][12][13][14] Their electrochemical properties in the Na cells have been clarified in detail and it was found that some layered materials can deliver large reversible capacity with good redox reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited layered materials showed high operating voltage so far. 10 Increase of operating voltage is an important strategy to increase the energy density of Na-ion batteries. In contrast to layered oxides, cobalt or vanadium phosphates and fluorophosphates containing sufficient sodium, such as Na 4 resulting in impurity phase of metallic cobalt and they did not report the electrode performance of the carbon-composite material.…”
Section: Introductionmentioning
confidence: 99%
“…20 In our previous study, we showed that P2-Na 22 In titanate based materials, low voltage sodium insertion has also been achieved using Ti 4+/3+ redox couple making them attractive as anode materials. 14,21,23 Formation of multiple phases is undesirable in intercalation materials as phase boundaries could potentially hinder ion transport compared to a single phase solid solution material.…”
mentioning
confidence: 99%
“…Sodium intercalation/deintercalation operates on the Ni 2+ /Ni 4+ redox couple. 7 Using this strategy, the formation of the Ni 3+ Jahn-Teller ion can be avoided in the synthesized pristine materials. Maximization of the active Ni 2+ ion content of cathode materials is a strategy that may lead to higher energy density.…”
mentioning
confidence: 99%
“…This O3-P3-O1 transition agrees well with past observations of Na 3 Ni 2 SbO 6 during charge. 7 It should be noted that even at the end of charging to 3.8 V, there is still significant amount of the pristine O3 phase remaining in the structure. Such phenomenon is indicative of the slow kinetics.…”
mentioning
confidence: 99%